Potency and Distribution of Meranti (Shorea spp.) in Protected Area of PT. Wana Hijau Pesaguan, West Kalimantan POTENSI DAN SEBARAN JENIS MERANTI (Shorea spp.) PADA KAWASAN LINDUNG PT. WANA HIJAU PESAGUAN, KALIMANTAN BARAT - Istomo .; Ma'shum Afnani (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2014)
Meranti (Shorea spp.) is a type of commercial timber. The existence of meranti in its natural habitat was decreasing because of illegal logging and exploitation. This research aim to assess the potency and distribution pattern of meranti species, to calculate diversity meranti and also to calculate biomass of meranti species at the protected area. The result of this research showed that the quantity of meranti species in proctected area as much as 13 species. Meranti density at the location of germplasm protected area as much as 31 individuals/ha, at the forest area with slope > 25 % as much as 48 individuals/ha, riparian left side as much as 25 individuals/ha and riparian right side as much as 9 individuals/ha. Distribution patterns generally group and uniform. Volume meranti are germplasm protected area as much as 2.63 m3/ha, at the forest area with slope > 25 % as much as 139.14 m3/ha, riparian left side as much as 30.59 m3/ha, riparian right as much as 26.90 m3/ha. Meranti total biomass on the location of germplasm protected area 9.15 tons/ha, at the forest area with slopes > 25% 127.87 tons/ha, riparian left side 27.34 tons/ha and riparian right side 29.7 tons/ha.Keyword: Distribution, Meranti (Shorea spp.), PT. Wana Hijau Pesaguan’s Protected Area, Potency